The Imperative and Reality of Constitutional Recognition for Indigenous Land Rights in Bangladesh - Sojol Ahmed Bappi (Law and Society Students' Journal)
Indigenous peoples of Bangladesh have been residing in the land of Bangladesh long before the demarcation of this land. They hold a deep belief that there exists a sacred connection between them and their ancestral lands, which usually passes through generations in the form of collective ownership. Due to the constitutional non-recognition of this form of ownership, they do not possess any legal right over these lands, and eventually, they have been facing forcible eviction from their ancestral lands. Though the Constitution has denied the indigenous identity and hasn’t incorporated collective land ownership in Articles 6 and 13, respectively, it still affirms that ensuring the socio-economic rights of the people and upholding the inherent dignity of people from their respective footings is the signature tune of the Constitution. This paper will evaluate how this constitutional non-recognition led to the forcible eviction of the indigenous people from their ancestral land, despite international legal instruments stressing the imperativeness of recognizing collective ownership of indigenous peoples. This paper will also explore how Article 7B of the Constitution has interpolated the last nail in the coffin of the aspiration of future recognition of the collective ownership of indigenous people and how this provision has faded away the fundamental aim and progressive thirst of the Constitution.